Immune Checkpoint Inhibitors and Lupus Erythematosus - Hans Vitzthum von Eckstaedt; Arohi Singh; Pankti Reid; Kimberly Trotter (MDPI AG, 2024)
Immune checkpoint inhibitors (ICIs) are the standard of care for a growing number of malignancies. Unfortunately, they are associated with a broad range of unique toxicities that mimic the presentations of primary autoimmune conditions. These adverse events are termed immune-related adverse events (irAEs), of which ICI-lupus erythematosus (ICI-LE) constitutes a small percentage. Our review aims to describe the available literature on ICI-LE and ICI treatment for patients with pre-existing lupus. Most diagnoses of ICI-LE had findings of only cutaneous lupus; four diagnoses of ICI-LE had systemic lupus manifestations. Over 90% (27 of 29) of cases received anti-PD-1/PDL-1 monotherapy, 1 received combination therapy, and 1 received only anti-CTLA-4 treatment. About three-fourths (22 of 29 or 76%) of patients with ICI-lupus were managed with topical steroids, 13 (45%) received hydroxychloroquine, and 10 (34%) required oral corticosteroids. In our case series, none of the patients with pre-existing lupus receiving ICI therapy for cancer had a flare of their lupus, but few had de novo irAE manifestations, all of which were characterized as low-grade. The review of the literature yielded seven ICI-LE flares from a total of 27 patients with pre-existing lupus who received ICI. Most flares were manageable without need for ICI cessation.